2009
DOI: 10.2460/javma.234.12.1525
|View full text |Cite
|
Sign up to set email alerts
|

Letters to the Editor

Abstract: label instructs, the calcium-to-phosphorus ratio becomes substantially inverted. In addition, vitamin D, another nutrient whose deficiency contributed to the disease in our puppy, was not and still does not appear to be supplemented in the premix.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Whyte et al [ 27 ] found a significant positive correlation between ALT and PD and a negative correlation between platelet count and PD. In addition to renal, hepatic and systemic inflammation, it has been suggested that PD may be associated [ 28 , 29 ] with increased risk for cardiovascular problems such as endocarditis and cardiomyopathy. For example, Glickman et al [ 28 ] reported that dogs with PD had a higher frequency of cardiovascular-related events and that the frequency increased with increasing severity of PD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whyte et al [ 27 ] found a significant positive correlation between ALT and PD and a negative correlation between platelet count and PD. In addition to renal, hepatic and systemic inflammation, it has been suggested that PD may be associated [ 28 , 29 ] with increased risk for cardiovascular problems such as endocarditis and cardiomyopathy. For example, Glickman et al [ 28 ] reported that dogs with PD had a higher frequency of cardiovascular-related events and that the frequency increased with increasing severity of PD.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Glickman et al [ 28 ] reported that dogs with PD had a higher frequency of cardiovascular-related events and that the frequency increased with increasing severity of PD. Others have questioned the validity of these results indicating more research is needed before definitive conclusions can be drawn [ 29 ]. These studies suggest that any degree of PD increases risk for several systemic diseases and merits concern.…”
Section: Discussionmentioning
confidence: 99%